Tinjauan Yuridis Kebijakan Conjugal Visit Dan Pengadaan Bilik Asmara Sebagai Upaya Preventif Pada Kasus Penyimpangan Seksual Oleh Narapidana Di Lembaga Pemasyarakatan - Lestari, Vidyah Erika; setianto, muhamad jodi; landrawan, i wayan (Jurnal Ilmu Hukum Sui Generis, 2024)
This research aims to (1) examine and analyze the regulation of the conjugal visit policy and the provision of love rooms as a preventive measure in cases of sexual deviation by prisoners in correctional institutions, and (2) to study and analyze the urgency of the existence of the conjugal visit policy and the provision of love rooms as a preventive steps related to the occurrence of sexual deviations in correctional institutions in Indonesia. The type of research in this research is normative legal research with the approaches taken being the statutory approach (statue approach), conceptual approach, comparative approach and case approach. The results of the research show that (1) legal regulations regarding the conjugal visit policy and the provision of love rooms in Indonesia are not regulated in statutory regulations even though prisoners as ordinary humans also need to fulfill their sexual needs as a basic need that must be fulfilled and nothing should hinder the state. Others have also implemented regulations regarding the conjugal visit policy and the provision of love rooms as a fulfillment of the basic rights of prisoners, and (2) the urgency of the conjugal visit policy and the provision of love rooms in Indonesia at this time, namely as a preventive measure in cases of sexual deviation and fulfillment of sexual needs for prisoners while they are serving their sentence and giving prisoners their rights as ordinary human beings who have basic needs so as not to violate existing norms which could later cause new problems with the presence of sexually transmitted diseases.